Conflicts between state and civil society related to infrastructure projects - Kathryn Ann Hochstetler (Institute for Applied Economic Research (ipea), 2016)
Environmental impact assessment is currently the major Brazilian institution that routinely seeks community input about infrastructure projects. It is criticized both by activists who think it permits projects it should not and by project proponents who think that it is too slow and blocks projects it should allow. In this paper, I evaluate how Brazilian environmental licensing works in practice as an institutional mechanism for resolving state conflicts with civil society over infrastructure projects. I draw on a recent study of community conflicts in 302 electricity projects there, showing that such conflicts are less common than often believed and happen in about 20 percent of the projects. Almost two-thirds of the protests are "informative" in nature, designed not to block the project but to communicate information about the effects of the project or its implementation, often long after licensing is complete. Almost two-thirds also raise socioeconomic issues rather than environmental issues per se. Given these characteristics of current community-based conflict, I explore a number of alternatives to current Brazilian licensing practices. Some, like new regulations on wind power plants or processes that seek free prior informed consent, show potential to productively address state-society conflict on projects, while others - like recent Congressional efforts to speed licensing - are only likely to displace conflict from institutional to non-institutional processes.
Keywords: D74; 330; environmental licensing; participation; socioenvironmental conflict; social movements; energy